Instructor's guide to accompany The art of floral design - Hunter, Norah T. (Delmar, 2000)
The Art of Floral Design, 2E is a fully illustrated color text designed to take the student from basic to advanced floral design techniques. With a well-balanced presentation of theory and practice this textbook sets the standard for teaching floral design techniques. Topics covered include the principles and mechanics of flower arranging, basic flower anatomy, as well as arrangement styles for a variety of special occasions. Updated to reflect the latest concepts and practices, this new second edition will place students at the forefront of floral design